Fungsi Kepala Desa Dalam Pengelolaan Dana Desa Di Desa Nobi-Nobi Kecamatan Amanuban Tengah Kabupaten Timor Tengah Selatan - Linome, Sari; Yohanes, Saryono; Tupen, Rafael Rape (Law Faculty, Nusa Cendana University, 2024)
This research has been carried out in Nobi-Nobi Village, Central Amanuban District, South Central Timor Regency in September 2023. The purpose of this study is to identify the role that village heads play in the management of village funds in Nobi-Nobi Village, Central Amanuban District, South Central Timor Regency, as well as the factors that inhibit this management. Both normative and empirical juridical legal methodologies were employed in this investigation. Primary and secondary data are the two categories and sources of data. Literature reviews, interviews, and observation are used as data collection methods. Tabulation, coding, and editing are the three steps in data processing. The results showed that the management of Village Funds in Nobi-Nobi Village, Central Amanuban District, South Central Timor Regency from the planning stage, the implementation stage to the accountability stage has not run optimally in compliance with village financial management regulation Number of 2018 issued by the minister of home affairs. Inhibiting factors in the management of Village Funds in Nobi-Nobi Village are, lack of human resources, incomplete facilities and infrastructure, lack of awareness from the community and tend not to understand and sources of income that only come from one source, namely transfer funds.